Efficacy of the RemoweLL cardiotomy reservoir for fat and leucocyte removal from shed mediastinal blood: a randomized controlled trial. (October 2016) - Lagny, Marc-Gilbert; Gothot, Andre; Hans, Gregory A.; Koch, Jean-Noël; Blaffart, Francine; Hella, Dominique; Donneau, Anne-Françoise; Roediger, Laurence; Lecut, Christelle; Pincemaïl, Joël; Cheramy-Bien, Jean-Paul; Defraigne, Jean-Olivier
Introduction: Re-transfusion of lipid particles and activated leucocytes with shed mediastinal blood (SMB) can aggravate cardiopulmonary bypass-associated inflammation and increase the embolic load. This study evaluated the fat and leucocyte removal capacity of the RemoweLL cardiotomy reservoir. Methods: Forty-five patients undergoing elective on-pump cardiac surgery were randomly allocated to filtration of SMB using the RemoweLL or the Admiral cardiotomy reservoir. The primary outcome was a drop in leucocytes and lipid particles obtained with the two filters. The effect of the filters on other blood cells and inflammatory mediators, such as myeloperoxidase (MPO), was also assessed. Results: The RemoweLL cardiotomy filter removed 16.5% of the leucocytes (p<0.001) while no significant removal of leucocytes was observed with the Admiral (p=0.48). The percentage reductions in lipid particles were similar in the two groups (26% vs 23%, p=0.2). Both filters similarly affected the level of MPO (p=0.71). Conclusion: The RemoweLL filter more effectively removed leucocytes from SMB than the Admiral. It offered no advantage in terms of lipid particle clearance.